Prior human endemic coronavirus exposure does not affect humoral responses to SARS-CoV-2 protein vaccines - Guy de Bruyn; Haritha Adhikarla; Caroline K. Brackett; Yichen Jia; Premkumar Lakshmanane; Sarah V. Mudrak; Sheetal Sawant; Donghui Zhang; Roman M. Chicz; Saranya Sridhar; Georgia D. Tomaras; Kelly E. Seaton (npj Vaccines)
Abstract We included measurement of pre-existing immunity to human endemic coronaviruses (HCoV) in a Phase I/II study of SARS-CoV-2 spike protein vaccine candidates. A Binding Antibody Multiplex Assay measured HCoV-specific IgG to the receptor binding domain or full-length spike of human coronaviruses HKU1, 229E, NL63, and OC43. We found no evidence for the impact of HCoV antibodies on neutralizing and binding antibody responses to the candidate SARS-CoV-2 vaccines.